Efektifitas Pembuatan Kompos Limbah Pabrik Teh Hijau (Tea Fluff) Menggunakan EM4 dan Pupuk Kandang Sapi - Restu Wulansari; Anni Yuniarti; Erdiansyah Rezamela (Soilrens, 2020)
One of the way to use green tea factory waste (tea fluff) as a source of plant nutrients is in the form of compost. The aim of this research was to get the appropriate composition of composting of green tea factory waste using a combination of EM4 and cow manure and composted for 5 weeks (35 days). This research was designed in randomized block with 6 treatments and four replications. Compositions of tea fluff and manure compost consisted of: P1 = Control; P2 = Tea Fluff + cow manure (1: 1); P3 = Tea Fluff + cow manure (1: 2); P4 = Tea Fluff + cow manure (1: 3); P5 = Tea Fluff + cow manure (2: 1); and P6 = Tea Fluff + cow manure (3: 1). Data related to composting process such as physical quality (color, texture, and odor) and chemical analysis (pH, C-organic, N-total and C/N ratio) were taken. Based on the results of daily temperature and pH fluctuations, composting proces ran normally. Based on the results of chemical analysis, the parameters of pH, organic C and N-total compost showed significant differences. Within 5 weeks, all compost parameters that have been analyzed chemically and the results has fulfilled the quality standards according SNI 19-7030-2004 standard. Combination of tea fluff:cow manure (3: 1) showed the highest C-organic and N-total results among all treatments.